Question
upstudy study bank question image url

6.1.2 Exam: Semester 2 Exam Question 40 of 40 What is the solution to \( \sqrt{7 x-4}=2 \sqrt{x} \) ? A. \( -\frac{4}{3} \) B. \( -\frac{4}{5} \) C. \( \frac{4}{5} \) D. \( \frac{4}{3} \)

Ask by Hardy Montgomery. in the United States
Jan 31,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution is \( x = \frac{4}{3} \), so the answer is D.

Solution

Solve the equation \( \sqrt{7x-4}=2\sqrt{x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\sqrt{7x-4}=2\sqrt{x}\) - step1: Find the domain: \(\sqrt{7x-4}=2\sqrt{x},x\geq \frac{4}{7}\) - step2: Swap the sides: \(2\sqrt{x}=\sqrt{7x-4}\) - step3: Rewrite the expression: \(\sqrt{x}=\frac{\sqrt{7x-4}}{2}\) - step4: Raise both sides to the \(2\)-th power\(:\) \(\left(\sqrt{x}\right)^{2}=\left(\frac{\sqrt{7x-4}}{2}\right)^{2}\) - step5: Evaluate the power: \(x=\frac{7x-4}{4}\) - step6: Cross multiply: \(x\times 4=7x-4\) - step7: Simplify the equation: \(4x=7x-4\) - step8: Move the variable to the left side: \(4x-7x=-4\) - step9: Subtract the terms: \(-3x=-4\) - step10: Change the signs: \(3x=4\) - step11: Divide both sides: \(\frac{3x}{3}=\frac{4}{3}\) - step12: Divide the numbers: \(x=\frac{4}{3}\) - step13: Check if the solution is in the defined range: \(x=\frac{4}{3},x\geq \frac{4}{7}\) - step14: Find the intersection: \(x=\frac{4}{3}\) - step15: Check the solution: \(x=\frac{4}{3}\) The solution to the equation \( \sqrt{7x-4}=2\sqrt{x} \) is \( x = \frac{4}{3} \). Therefore, the correct answer is D. \( \frac{4}{3} \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( \sqrt{7x - 4} = 2\sqrt{x} \), we can start by squaring both sides to eliminate the square roots. This gives us: \[ 7x - 4 = 4x \] Next, we'll isolate \( x \) by moving the \( 4x \) to the left side: \[ 7x - 4x = 4 \] This simplifies to: \[ 3x = 4 \] Dividing both sides by 3 gives us: \[ x = \frac{4}{3} \] We have to check if this solution is valid by substituting back into the original equation. When we substitute \( x = \frac{4}{3} \): Left side: \[ \sqrt{7\left(\frac{4}{3}\right) - 4} = \sqrt{\frac{28}{3} - 4} = \sqrt{\frac{28}{3} - \frac{12}{3}} = \sqrt{\frac{16}{3}} \] Right side: \[ 2\sqrt{\frac{4}{3}} = 2 \cdot \frac{2}{\sqrt{3}} = \frac{4}{\sqrt{3}} = \frac{4 \sqrt{3}}{3} \] After rationalizing the left side, we find they equate. Thus, the solution \( x = \frac{4}{3} \) is valid. Therefore, the answer is D. \( \frac{4}{3} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy